Hypocalcaemia following total thyroidectomy: An analysis of 806 patients - C Gopalakrishnan Nair (Indian Journal of Endocrinology and Metabolism, 2013)
Background: Permanent hypocalcaemia following thyroidectomy causes considerable morbidity. This prospective observational study aims to define the factors likely to predict hypocalcaemia following total thyroidectomy. Materials and Methods: Patients who were subjected to total thyroidectomy during January 2005 to December 2009 were followed up for a minimum period of 1 year. Efficacy of an intraoperative parathyroid hormone assay to predict hypocalcaemia was validated. Results: Overall incidence of hypocalcaemia was 23.6% ( n = 190) and that of permanent hypocalcaemia was 1.61% ( n = 13). Onset was delayed up to 3 rd postoperative day in 13 patients. Hypocalcaemia was significantly associated with thyroidectomy for Grave′s Disease ( P = 0.001), Hashimoto′s thyroiditis ( P = 0.003), and with incidental parathyroidectomy ( P = 0.006). The intraoperative assay of parathyroid hormone showed low sensitivity (0.5) and satisfactory specificity (0.9) in predicting hypocalcemia. Conclusion: Hypocalcemia could manifest late in the immediate postoperative period and this may explain latent hypocalcemia. High incidence of hypocalcaemia noted in Grave′s Disease could be due to the autoimmunity since same feature was noted associated with Hashimoto′s thyroiditis and the incidence of hypocalcaemia was not high in the subgroup with toxic nodular goiter. The incidence of hypocalcemia was not affected by age or sex.